Training, opportunity and constraints for social science research in women health and coordinated care for DM patients with periodontal disease in primary care practices - Tin, Myo Han (2015)
Background: Social science research is research concerning with social science disciplines including the sociology of health (inequalities in health, experiences of health and health care system); social anthropology on health (society’s belief and practices relating to health and illness); the role of health and illness in social history, and to policy studies in the health arena. Thus, social science research has become an accepted part of health research including primary care research. Health professionals have integrating insights from social science research into their understanding of human health determined by social factors to assist in providing holistic care. In this symposium, opportunity, training and constraints of primary care physicians (PCPs) in social science research to provide evidences for holistic care of women patients and DM patients with periodontal diseases in primarycare practices will be presented. Discussion: PCPs have potential to address the social determinants of health because of trusted doctor-patient relationship which is obtained providing patient-centered comprehensive and coordinated care. Results of clinical and community research on women health and DM patients with PD highlighted to explore socio-cultural factors as further studies to get evidences for its effect on health. However, it is noticed that continuing of social science health research collaborated with other disciplines by PCPs themselves is very rare in primary care setting. In Myanmar, proper hand-on research training for GPs has been still limited and consequently case presentation, case series and project orientated community survey using quantitative methods are most research done by GPs. In Malaysia, primary care research and training are more advanced in line with development of family medicine than those of Myanmar. Constraints of GPs to conduct social science research in Myanmar were low awareness, limited experiences on research methodology including statistics, time and no research grant. Besides, it was not easy for GPs to conduct a research project applying qualitative method to explore the socio-anthropological insights of the patients. Conclusion: Encouragement, hands-on qualitative research training, technical and financial support are essential to promote awareness and participation of PCPs in social science health research collaborated with other disciplines.